2018
DOI: 10.1186/s13104-018-3458-7
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the short physical performance battery following pulmonary rehabilitation in patients with chronic obstructive pulmonary disease

Abstract: ObjectiveThere is a need for simple tools to evaluate physical performance in patients with COPD before and after pulmonary rehabilitation. The aims of this study were to evaluate changes in short physical performance battery (SPPB)-scores in patients with COPD after a 4-week pulmonary rehabilitation program; explore possible relationships between SPPB-scores and exercise capacity (6-min walk distance), dyspnea (modified Medical Research Council’s dyspnea scale), disease-specific quality of life (COPD assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
(35 reference statements)
5
22
0
1
Order By: Relevance
“…Thirdly, SPPB can have a ceiling effect affecting highly functioning patients. 9 In this study, 25.6% of the subjects had a full score on SPPB, and the effect of the ceiling effect of SPPB can't be denied. Therefore, SPPB may not be suitable for highly functional patients awaiting lung resection surgery.…”
Section: Discussionmentioning
confidence: 62%
“…Thirdly, SPPB can have a ceiling effect affecting highly functioning patients. 9 In this study, 25.6% of the subjects had a full score on SPPB, and the effect of the ceiling effect of SPPB can't be denied. Therefore, SPPB may not be suitable for highly functional patients awaiting lung resection surgery.…”
Section: Discussionmentioning
confidence: 62%
“…This is anticipating 30% lost to follow-up or death at the 12-month assessment. This sample size estimation is based on previous literature utilizing the Short Performance Physical Battery (SPPB) score [ 12 , 22 25 ]. Assuming a mean SPPB score of 6.0 (SD 2.5), a sample size of 150 is needed to obtain 80% power and to detect a change score of 0.81, using a two-sample t test at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Among the results obtained, poor physical performance in the sit-and-rise test increased the likelihood of occurrence of moderate to severe dyspnea by 85% among older individuals when they exerted effort. This result suggests that an association between lower-limb function and the sensation of dyspnea was present even after adjustment for frailty condition.Similarly, Larsson et al5 detected a significant correlation between better physical performance in the sit-and rise test (assessed using the SPPB) and lower dyspnea scores (from the mMRC) among patients of average age with chronic obstructive pulmonary disease (COPD) aged on average 69 ± 6 years. Although the health condition of the population evaluated in their study differed from that of the present sample, their finding is supported by our results.…”
mentioning
confidence: 92%
“…Among the factors that favor the onset of this symptom, reduced exercise tolerance and a low level of physical activity seem to contribute to a decline in physical performance during activities of daily life. 2,4 Vaz Fragoso et al 4 and Larsson et al 5 reported that poor physical performance assessed on the basis of lower-limb performance in physical tests such as sitting and rising from a chair is associated with an increase in dyspnea among both robust older adults and older adults with frailty and/or chronic obstructive pulmonary disease (COPD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation